A Retrospective Case Series of a Novel Spinal Cord Stimulator Trial Technique with Less Displacement and Migration of the Trial Leads - N. Shaparin; K. Gritsenko; P. Agrawal; S. Kim; S. Wahezi; A. Gitkind; J. Hascalovici; A. Vydyanathan; J. Bernstein; A. Dizdarevic; N. Mehta; A. Kaufman (Pain Research and Management)
Background. Spinal cord stimulation is an established treatment option for certain chronic pain conditions which have been previously unresponsive to conservative therapies or potentially for a subset of patients who have not improved following spine surgery. Prior to permanent lead implantation, stimulator lead trials are performed to ensure adequate patient benefit. During these trials, one of the most common complications and reasons for failure is the displacement and migration of the trial leads, resulting in lost therapeutic coverage. Other complications include infection and dislodged bulky dressings. There is a paucity of literature describing an adequate procedural method to prevent these common complications. Objective. This study utilizes a series of 19 patients to evaluate a new technique for securing percutaneous spinal cord simulator trial leads, which may minimize dislodgement and migration complications and improve the rate of trial success. Study Design. Retrospective case series. Setting. New Jersey Medical School, Department of Anesthesiology, Pain Management Division. Methods. A retrospective chart review was conducted on 19 consecutive patients undergoing placement of the percutaneous thoracic spinal cord stimulator trial leads for pain associated with lumbar spine pathology over a two-year period (2010–2012). Results. Of the 19 patients in our cohort, there was one trial lead displacement, no lead migrations, and no site infections. Thirteen patients went on to permanent lead implantation. This improved trial lead placement technique had a high success rate with a low number of complications. Limitations. Small sample size, retrospective case series, and no control group for comparison. Conclusion. This case series was able to demonstrate that our described novel spinal cord stimulator trial lead placement and dressing technique can decrease the incidence of lead displacement and migration, thus improving trial success.